A trade-off between old-age financial adequacy and state budget sustainability: Searching a government optimum solution to the pension system in Indonesia - Ahmad Irsan A. Moeis; Nachrowi Djalal Nachrowi; Aris Ananta; Vid Adrison (Cogent Economics & Finance)
A generous PAYG defined benefit pension system can guarantee retirees to have comfortable life, but the state budget may not be sustainable when the population is ageing. On the other hand, a defined contribution pension system guarantees state budget sustainability, but making retirees’ standard of living depends fully on their labour market performance (before retiring). The choice is even more difficult in developing countries with low budgets such as Indonesia. The defined contribution system is even more uncertain in promising old-age financial adequacy as people’s income and investment rates are low. This paper uses a simple OLG model to find an optimal solution from the government perspective—how much state budget should be allocated for the PAYG defined benefit system. It concludes that with a small state budget allocation, as part of a PAYG defined contribution system, to supplement a defined contribution system, the government of Indonesia can guarantee that retirees will not live under poverty while maintaining the state budget sustainability. It recommends that Indonesia combine a defined contribution system, to make a sustainable state budget, and a small budget allocation for a defined benefit system, to ensure that there is no old age poverty.